Islam and higher education: the role of Islamic-based universities in urban development / Nur Rafidah Asyikin Idris (2015)
The role of higher education and universities in societal development are characteristically very dynamic. In the context of urban development, there are voluminous materials on the role of universities (western model) in the development of urban areas. But not much have been written on the role of Islamic-based universities in the era of globalization and internationalization. Arguably, based on the western model, and in the context of Malaysia, higher education institutions in particular universities, functioned to produce employable graduates. But in the context of the developing countries, universities have a developmental role too, in particular, the development of areas in which they are located. This can be beyond employment consideration. Using Kuala Lumpur city-region as a case study, this paper examines the role of Islamic-based universities in urban development in comparison with universities which are based on the western model. The findings should contribute in some ways to formulating an explanatory framework to investigate the role of Islamic-based universities in urban development.